2020
DOI: 10.1103/physreve.101.053202
|View full text |Cite
|
Sign up to set email alerts
|

Gain of electron orbital angular momentum in a direct laser acceleration process

Abstract: Three-dimensional "particle in cell" simulations show that a quasistatic magnetic field can be generated in a plasma irradiated by a linearly polarized Laguerre-Gauss beam with a nonzero orbital angular momentum (OAM). Perturbative analysis of the electron dynamics in the low intensity limit and detailed numerical analysis predict a laser to electrons OAM transfer. Plasma electrons gain angular velocity thanks to the dephasing process induced by the combined action of the ponderomotive force and the laser indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…It was also demonstrated that Laguerre-Gaussian beams transfer a part of their OAM to electrons through the dephasing process similar to the direct electron acceleration (DLA) in Gaussian beams [15]. Vacuum-based charge acceleration with Laguerre-Gaussian beams has also been studied very recently [16,17] showing that it is possible to generate GeV high-quality electron bunch with low spread in energy and radial deflection.…”
Section: Introductionmentioning
confidence: 97%
“…It was also demonstrated that Laguerre-Gaussian beams transfer a part of their OAM to electrons through the dephasing process similar to the direct electron acceleration (DLA) in Gaussian beams [15]. Vacuum-based charge acceleration with Laguerre-Gaussian beams has also been studied very recently [16,17] showing that it is possible to generate GeV high-quality electron bunch with low spread in energy and radial deflection.…”
Section: Introductionmentioning
confidence: 97%
“…Recent work has analyzed the motion of free electrons in a LG beam in more detail, expanding to first and second order perturbations [13,15]. It was shown that angular momentum can be transferred to free electrons in LP LG beams when considering second order terms in the equations of motion; the electron gains and loses angular momentum but averaging over one laser cycle yields zero net angular momentum transfer.…”
Section: Coupling Of High Intensity Angular Momentum To Plasmamentioning
confidence: 99%
“…If the pulse is circularly polarized (CP) and of relativistic intensity, the generated magnetic field strength can be on the order of 100's of Tesla, last several picoseconds, and extend over millimeter scales [1]. The IFE has been studied extensively with CP beams both theoretically [2][3][4][5][6][7][8], and experimentally [1,9,10]; yet the effect is not exclusive to CP beams but also applicable to lasers carrying orbital angular momentum (OAM) [11][12][13]. Currently, we only know of one analytic model describing OAM driven magnetic fields and its transverse profile [11], but has not been verified numerically or experimentally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was also demonstrated that Laguerre-Gaussian beams transfer a part of their OAM to electrons through the dephasing process similar to the direct electron acceleration (DLA) in Gaussian beams [15]. Furthermore, the propagation of optical beams with OAM leads to plasma waves that may also carry OAM which couple to the plasma electrons and involve Landau damping and particle acceleration accompanied with the generation of quasi-static axial and azimuthal magnetic fields [16].…”
Section: Introductionmentioning
confidence: 99%